2015
DOI: 10.1093/cid/civ779
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyolysis in Ebola Virus Disease. Results of an Observational Study in a Treatment Center in Guinea

Abstract: Rhabdomyolysis is a frequent disorder in EVD and seems to be more common than in other viral infections. It may contribute to the renal failure observed in nonsurviving patients. More studies are needed to determine the impact of rhabdomyolysis on EVD outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 31 publications
5
13
2
Order By: Relevance
“…Changes in renal function were also observed in some patients, particularly during severe disease, as illustrated by the high levels of creatinine and blood urea nitrogen and their highly significant correlation. However, unlike other studies (4,5,8), we found that there was no significant correlation between high creatinine levels and a fatal outcome. Nevertheless, we found that the levels of both products increased during the course of the disease in fatal cases, suggesting that renal failure is a common feature of the terminal stages of EVD.…”
Section: L I N I C a L M E D I C I N Econtrasting
confidence: 99%
See 2 more Smart Citations
“…Changes in renal function were also observed in some patients, particularly during severe disease, as illustrated by the high levels of creatinine and blood urea nitrogen and their highly significant correlation. However, unlike other studies (4,5,8), we found that there was no significant correlation between high creatinine levels and a fatal outcome. Nevertheless, we found that the levels of both products increased during the course of the disease in fatal cases, suggesting that renal failure is a common feature of the terminal stages of EVD.…”
Section: L I N I C a L M E D I C I N Econtrasting
confidence: 99%
“…Levels of AST, and, to a lesser extent, ALT, appeared to be the most powerful markers of severity during EVD in our cohort. A similar observation was previously reported for EBOV and SUDV (3)(4)(5)8). Striking differences were observed in the patterns of change in biological analyte levels associated with tissue damage during disease.…”
Section: L I N I C a L M E D I C I N Esupporting
confidence: 88%
See 1 more Smart Citation
“…The abnormal electrolyte levels may result from profuse diarrhea, prerenal kidney dysfunction from dehydration, or direct acute kidney injury (AKI) from EVD. Beyond the direct effects of the virus on the kidney, EVD has been associated with rhabdomyolysis, which can cause AKI and subsequent electrolyte abnormalities [20]. …”
Section: Discussionmentioning
confidence: 99%
“…Because of the severity of EVD, a fair amount of patients may require intensive care. As recently shown in two reports, renal failure and rhabdomyolysis were frequent in severe EVD cases [4,5]. Common ICU therapy, including fluid therapy and dialysis, would help decrease mortality rates [6,7].…”
Section: Introductionmentioning
confidence: 79%